Design of Web-Based Information System for Jemaat Hidup Baru Salatiga Baptist Church - Welli; Sitokdana, Melkior N. N. (Infact: International Journal of Computers, 2025)
The use of the web as a medium for disseminating information has been utilized, both by individuals and institutions. Churches are one of the religious institutions that utilize the web as a medium for disseminating information. JHB Salatiga Baptist Church does not yet have a web as a means of delivering information to its congregation. Information about the church and service activities has not been documented and is only delivered directly after Sunday worship. Therefore, supporting information media is needed that can support the delivery of information as a whole and can be accessed at any time so that it is more effective and efficient. In this research, the method used is the waterfall method. And this research uses the bootstrap 4 framework and for the testing method using black box. The result of the research with the title "Design of Web-Based Information System of Jemaat Hidup Baru Salatiga Baptist Church", is a web design of JHB Salatiga Church for the delivery of information that makes it easy for congregants to access information effectively and efficiently.